Influence of Electromagnetic Field on Decoherence in Impurity Center Semiconductor Quantum Dot by Confined Spherical Gaussian Potential - Xin, Wei (International journal of theoretical physics, 2022)
The dependence of the temperature and electromagnetic field on the decoherence of quantum superposition states in a donor-center quantum dot with a double-parametric spherical Gaussian confinement potential is investigated based on the Lee-low-pines unitary transformation. The energies and wave functions of the ground state and the first excited state of the system are derived by using the Pekar type variational method. Then a superposition state of a two-state system is constructed. Two measures are introduced to quantify the decoherence of quantum superposition states: the ground-state decay time (lifetime) and the excited transition probability. The laws and mechanisms of the effects of the materials’ inherent properties, such as the dielectric constant ratio and the electron-phonon coupling constant, and environmental factors like temperature and electromagnetic field on the decoherence of superposition states are revealed through numerical calculation. This work improves the measurement method of the decoherence of superposition states, moreover, makes helpful exploration of a new scheme to suppress the decoherence of the qubit of the semiconductor quantum dot.